Silvicultura adaptiva y determinación de un ciclo de corta óptimo (técnico‑económico) en bosques naturales de la Región Huetar Norte, Costa Rica - Meza Picado, Víctor (2026)
[Introduction]: We present a technical–ecological and technical–economic analysis to determine an optimal harvesting cycle in natural forests. The study integrates 25 years of silvicultural monitoring with the development and calibration of an explicit silvicultural model (stand dynamics and management response) and an economic analysis based on the Forest Value (FV). [Objective]: To determine an optimal harvesting cycle in natural forests of the Huetar Norte Region through the development and validation of a silvicultural model that integrates structural indicators, growth dynamics, and technical–economic analysis under criteria of sustainability and national regulations. [Methodology]: By analyzing technical indicators required by national regulations—floristic similarity of commercial species, minimum basal area, and proportion of ephemeral heliophilous species (HE)—a 13-year harvesting cycle is justified, two years shorter than the legally established framework. The model incorporates an idealized growth function and two intermediate commercial silvicultural interventions (years 4 and 8), allowing maximum growth potential to be maintained, competition to be reduced, and intermediate revenues to be generated. The FV was calculated by capitalizing net income flows from successive rotations discounted at a reference rate. A sensitivity analysis was included to evaluate variations in extracted volumes. [Results]: The economic analysis using FV shows profitability 53.5% higher in the normal forest compared with the real forest. [Conclusions]: These results suggest that technical, intensive, and adaptive silviculture can enhance profitability without compromising the ecological integrity of the ecosystem.